2005
DOI: 10.1080/03079450500179715
|View full text |Cite
|
Sign up to set email alerts
|

Novel criteria for the diagnosis of Marek's disease virus-induced lymphomas

Abstract: Several novel criteria have been tested to assist in the differential diagnosis of tumours induced by Marek's disease virus (MDV) from those induced by avian leukosis virus (ALV) and reticuloendotheliosis virus (REV). A collection of tumours induced by inoculation of specific strains of MDV, ALV and REV, alone or in combination, were tested for quantification of MDV DNA by real-time polymerase chain reaction, expression of the MDV oncogene Meq, expression of several cell markers associated with transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Previous studies revealed that LAT and miRNA cluster 2 in GaHV-2 are abundantly expressed during the latency and lymphomagenesis stages of viral infection (Burnside et al 2006(Burnside et al , 2008Xu et al 2008). Although p53 is considered to be a major tumor repressor, it has been shown that nonmutated p53 is present in GaHV-2-induced lymphomas (Gimeno et al 2005). Further experiments are required to investigate the apparent contradiction between the production of native p53 and the development of lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that LAT and miRNA cluster 2 in GaHV-2 are abundantly expressed during the latency and lymphomagenesis stages of viral infection (Burnside et al 2006(Burnside et al , 2008Xu et al 2008). Although p53 is considered to be a major tumor repressor, it has been shown that nonmutated p53 is present in GaHV-2-induced lymphomas (Gimeno et al 2005). Further experiments are required to investigate the apparent contradiction between the production of native p53 and the development of lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…The number of MDV genome copies measured in this study is in broad agreement with recent reports (Baigent et al ., 2005;Gimeno et al ., 2005). Viral titres have been shown to be lower in PBL than spleen cells and feather follicle epithelium (Davidson & Borenshtain, 2003;Baigent et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, evaluation of effects of MeqGCN on cytolytic infection is difficult because Meq expression is not essential for early cytolytic infection (25). Meq is not always detected early in infection, and expression of Meq in vivo is variable and has been shown to depend on the virus strain and chicken line used (8,26). Since the FFE is the site of fully productive infection and source of horizontal transmission (4), we evaluated the role of Meq homodimers on transmission by IHC (Fig.…”
Section: Discussionmentioning
confidence: 99%